2018
DOI: 10.1080/02670836.2018.1444923
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and microhardness in horizontally solidified Al–7Si–0.15Fe–(3Cu; 0.3Mg) alloys

Abstract: Transient horizontal directional solidification (THDS) experiments have been carried out with Al–7wt.%Si–0.15Fe, Al–7wt.%Si–3wt.%Cu–0.15wt.%Fe and Al–7wt.%Si–0.3wt.%Mg–0.15wt.%Fe alloys, to identify experimental relationships between growth rates ( GR), cooling rates ( CR), tertiary dendrite arm spacings (λ3) and microhardness (HV). Optical microscopy and scanning electron microscopy/energy-dispersive spectrometry (SEM/EDS) were used to perform a comprehensive microstructural characterisation of the β-Al5FeSi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…It is observed that higher HV values were obtained in the interdendritic regions, in which Si + π + θ particles of high hardness are present. Vasconcelos et al 48 , Araújo et al 28 and Souza et al 40 have found higher HV values for Al-Si multicomponent alloys with addition of Cu and Mg and the authors have attributed to the presence of intermetallic phases (Al 2 Cu and Mg 2 Si) of high hardness in the interdendritic region of the as-solidified samples. In contrast to the procedure adopted in the present study, these authors did not perform HV measurements in the Al-rich and eutectic phases, the HV values reported by them were the means of 20 measurements obtained directly in the casting samples.…”
Section: Resultsmentioning
confidence: 96%
“…It is observed that higher HV values were obtained in the interdendritic regions, in which Si + π + θ particles of high hardness are present. Vasconcelos et al 48 , Araújo et al 28 and Souza et al 40 have found higher HV values for Al-Si multicomponent alloys with addition of Cu and Mg and the authors have attributed to the presence of intermetallic phases (Al 2 Cu and Mg 2 Si) of high hardness in the interdendritic region of the as-solidified samples. In contrast to the procedure adopted in the present study, these authors did not perform HV measurements in the Al-rich and eutectic phases, the HV values reported by them were the means of 20 measurements obtained directly in the casting samples.…”
Section: Resultsmentioning
confidence: 96%
“…Microstructural scale, phases morphology and heat treatment are conducive to change the properties of automotive AlSiMg alloy separately or in conjunction with each other, to develop desired and optimum properties in the casting. In this regard, a series of works were recently developed with the automotive casting Al7Si0.3Mg (wt.%) alloy, which in a rst stage aimed to analyze the effects of solidi cation conditions on the microstructure and mechanical properties [20][21][22][23]. In this step, the in uence of the thermal solidi cation parameters, such as growth and cooling rates on the length of the dendritic microstructure as well as on the size, distribution and morphology of the Mg 2 Si/Fe intermetallic compounds (ICMs) and, in turn, on the hardness and tensile properties were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this step, the in uence of the thermal solidi cation parameters, such as growth and cooling rates on the length of the dendritic microstructure as well as on the size, distribution and morphology of the Mg 2 Si/Fe intermetallic compounds (ICMs) and, in turn, on the hardness and tensile properties were investigated. In a second stage [6, 19,24], T6 heat treatment under different conditions has been applied to the as-cast samples resulting from the work of References [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, uma interessante característica adicional do sistema horizontal é o gradiente de concentração de soluto bem como os efeitos de densidade na direção vertical, uma vez que o líquido enriquecido de soluto, dependendo de sua densidade, pode decantar ou não, ao passo que o solvente tende a emergir devido as forças de flutuabilidade. Além disso, devido os efeitos impostos pela convecção termossolutal, sempre vai ocorrer um gradiente de temperaturas na direção vertical [14,[29][30][31][32][33]. Na literatura, observa-se que a grande maioria dos estudos desenvolvidos dedicam-se a investigar a formação de estruturas dendríticas obtidas durante a solidificação unidirecional de materiais metálicos somente nos sistemas verticais considerando o regime estacionário de extração de calor.…”
Section: Introductionunclassified